A study of morphometric variations of fallopian tube in female foetuses - Sarada, Toleti; Karey, Geetha Devi Venkatanaga; Karey, Geetha Devi Venkatanaga; Rayudu, Raja Madhava; Rayudu, Raja Madhava (International Journal of Research in Medical Sciences, 2017)
Background: Purpose of current study was to describe the variations found in the development, anatomical functional aspect of fallopian tube in the embryonic life and further development in the adult. This is about fundamental significance in treatment of infertility. Methods: The study is done on 30 embalmed dead female foetuses which were explored by gross dissection. The following data are noted from each specimen- length of tube, relation of tubes on both sides, number of fimbria and anomalies i.e. absence of tube (Agenesis). Results: In the thirty specimens studied the length of the tube is approximately 5-8 cm. The ampulla of 3rd trimester foetuses found to be convoluted. The convolutions are not so much marked in the 1st and 2nd trimester foetuses. In one foetus No 9 there is complete absence of left side tube. Another foetus No 20 tube length is 1 cm with absence of ampulla, infundibulum and fimbria on the right side, that is 6% congenital absence of one sided tube. The number of fimbria are in an average of 4-5 on both sides. Morgangi cysts present in tubes of 3 foetuses i.e. (9%). Conclusion: Majority of the foetuses length of the fallopian tubes vary from 5-8 cm. Single tube absent in two foetuses, one foetus left side complete absence and another foetus right side absence of ampulla, infundibulum and fimbria i.e. of about 6% congenital absence of tube is important for obstetricians for treating infertility.